Supply Chain Strategies, Issues and Models - Ramanathan, Usha.; Ramanathan, Ramakrishnan; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2014)
In the 21st century, supply chain operations and relationships among supply chain partners have become highly challenging, necessitating new approaches, e.g., the development of new models. Supply Chain Strategies, Issues and Models discusses supply chain issues and models with examples from actual industrial cases. Expert authors with a wide spectrum of knowledge working in various areas of supply chain management from various geographical locations offer refreshing, novel and insightful ideas and address possible solutions using established theories and models. Supply Chain Strategies, Issues and Models features studies that have used mathematical modeling, statistical analyses and also descriptive qualitative studies. The chapters cover many relevant themes related to supply chains and logistics including supply chain complexity, information sharing, quality (six sigma), electronic Kanbans, inventory models, scheduling, purchasing and contracts. To facilitate easy reading, the chapters that deal with supply chain related issues are first, followed by studies on inventory, scheduling, purchasing and logistics. This book can be used as a useful resource of supply chain management by academics, students and practitioners. This book can serve as a helping tool in managerial decision making for investments in collaboration and information exchange to improve forecasts, scheduling and inventory management, and for supply chain managers to leverage product and process complexities into competitive advantage. Some interesting mathematical models can appeal to students and researchers interested in modeling the impact of information sharing in supply chains.
Supply Chain Complexity And Strategy -- A systematic approach to analyze the information in supply chain collaboration: A conceptual framework -- The Value Of Information Sharing In A Multi-Stage Serial Supply Chain With Positive And Deterministic Lead Times -- Six Sigma in Supply Chain -- A Case Study on E- Kanban implementation: A framework for successful implementation -- A Comparative Study Of Periodic- Review Order-Up-To (T, S) Policy And Continuous-Review (S, S) Policy In A Serial Supply Chain Over A Finite Planning Horizon -- Modeling Of Scheduling Batch Processor In Discrete Parts Manufacturing -- Cooperative Purchasing in Small and Medium-sized Enterprise (SMEs) -- Supply Chains with Service Level Agreements -- The role of logistics in e-commerce transactions: An exploratory study of customer feedback and risk -- Supply Chain Strategies in Difficult Times.
Keywords: Engineering; Engineering economy; Engineering; Engineering Economics, Organization, Logistics, Marketing; Production/Logistics/Supply Chain Management; Innovation/Technology Management